Studi Literatur: Analisis Estetika Musik Barok pada "Feel My Rhythm” - Cevinita Nahany Nevia Nikita Becker; Maula Waytisi Kirana; Axel Nicholas Cornelius (TAMUMATRA, 2023)
Music, fundamentally, always evolves through increasing human creativity. The increase in human creativity has given rise to various variations of popular music trends. This is found in the use of Baroque music samples "Air on the G String" by Johann Sebastian Bach in the song "Feel My Rhythm" by the girl group Red Velvet. This study examines the aesthetic value of Baroque music "Air on the G String" by Johann Sebastian Bach in its utilization on the song "Feel My Rhythm" by Red Velvet. As qualitative research, the assessment was conducted using a literature study approach and descriptive analysis method. Through research, it was found that there are key adjustments, chord progressions, bass and harmony agility, as well as electronic sound medium intervention in the song "Feel My Rhythm" through the aesthetic perspective of Baroque music "Air on the G String." Thus, in the use of samples of Baroque music "Air on the G String" in the Modern era "Feel My Rhythm," it can be concluded that the aesthetic authenticity (characteristics) of Baroque music is still present and only given an increase in modernity aspects.